Cell migration is impaired in XPA‐deficient cells. Issue 2 (12th December 2022) - Takeuchi, Seiji; Fukumoto, Takeshi; Takemori, Chihiro; Saito, Naoaki; Nishigori, Chikako; Sato, Makoto
Abstract: Xeroderma pigmentosum (XP) is a hereditary disorder characterized by photosensitivity, predisposition to skin cancers, and neurological abnormalities including microcephaly and progressive neurodegeneration. A lack of nucleotide excision repair (NER) in patients with XP can cause hypersensitivity to the sun, leading to skin cancer, whereas the etiology of the neuronal symptoms of XP remains ambiguous. There are various neurological disorders that perturb neuronal migration, causing mislocalization and disorganization of the cortical lamination. Here, we investigated the role of the XP group‐A ( Xpa ) gene in directed cell migration. First, we adopted an in utero electroporation method to transduce shRNA vectors into the murine embryonic cerebral cortex for the in vivo knockdown of Xpa . Xpa‐ knockdown neurons in the embryonic cerebral cortex showed abnormal cell migration, cell cycle exit, and differentiation. The genotype–phenotype relationship between the lack of XPA and cell migration abnormalities was confirmed using both a scratch assay and time‐lapse microscopy in XP‐A patient‐derived fibroblasts. Unlike healthy cells, these cells showed impairment in overall mobility and the direction of motility. Therefore, abnormal cell migration may explain neural tissue abnormalities in patients with XP‐A. Abstract : We found that Xpa ‐knockdown neural cells show delayed migration in the developmental stage of the neonatal cortex. The genotype–phenotype relationship between the lack of XPA cell migration abnormalities was confirmed using both a scratch assay and time‐lapse microscopy in XP‐A patient‐derived fibroblasts. The abnormal cell migration may explain neural tissue abnormalities in patients with XP‐A.